Perception towards importance of information and communication technology among rural administrators - Mohamed Shaffril, Hayrol Azril; Abu Samah, Bahaman (Friends Science Publishers, 2009)
This study was conducted to examine the perception of Village Development Committee (VDC) in realizing sustainable development of rural community in Village Vision Movement (VVM) village and factors that affect it in three zones representing three states in Peninsular Malaysia. States selected were Selangor (central zone), Negeri Sembilan (southern zone) and Pahang (east coast zone). Six villages were selected from each state and the village selected were from villages listed in Village Vision Movement (VVM). A total of 235 respondents were chosen for this study. Overall, members of VDC perceived Information and Communication Technology or ICT from moderate to high in term of their importance for their village development. Zone, where respondents stayed had been identified to have significant difference in their perception towards the importance of ICT, while income per month of the VDC members indicated positive and significant relationship with their perception towards the importance of ICT.